O letramento para a competência informacional em bibliotecas escolares: estudo a partir dos projetos políticos-pedagógicos dos colégios de aplicação das universidades federais brasileiras - Niliane Cunha de Aguiar (2018)
Understanding the need of integrating the school library with the pedagogical proposal of the schools and the importance of the training for the informational competence of the students of contemporary society, this research analyzes the perspectives of the political and pedagogical projects (PPP) of the colleges of application of the Brazilian federal universities about the possibilities of development of literacy for informational competence. Assuming that the political-pedagogical projects of schools should include the activities developed by school libraries, and that such activities currently include literacy for informational literacy, the research problem arises from the need to analyze this premise in order to understand how the school library and its activities are presented in those documents. It is believed that this presentation demonstrates the perspective that the education sector in Brazil has regarding the role and importance of the library in the school context. The response presented in the study may contribute to the development of new public information policies for school libraries. Therefore, a content analysis was carried out, the result of which was based on the conclusions drawn. federal universities, the same, in their political-pedagogical projects do not differ from other Brazilian public schools in relation to the importance given to the school library as a space for development of literacy for informational competence, that is, libraries are not yet visualized as a pedagogical space and the school librarian is not seen as a contributor to the educational process. This is one of the challenges of implementing the Brazilian law 12.244 / 2010 that determines the compulsory existence of libraries in all Brazilian schools by 2020, and for this reason needs to be explored by professionals in the area of Information Science and also by professionals in the area of Education. What is proposed is that the value of collaborative work is the goal of these areas and especially of the courses of librarianship and pedagogy, so that in the future, from basic education, students can reap the fruits of this partnership, which will be the fulfillment of the dream informational literacy.